PENGELOLAAN SARANA PEMBELAJARAN DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) MITRA RIAU JAYA CEMERLANG KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Rahayu, Ica; Jas, Jaspar; Wilson, Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: Problem formulation in this research is how is the management oflearning facilities in PKBM Mitra Riau jaya Cemerlang Marpoyan Damai DistrictPekanbaru City? This aims to determine the Management of Learning Facilities in theCommunity Learning Activity Center (PKBM) of Riau Jaya Cemerlang, MarpoyanDamai District, Pekanbaru City. This study uses a qualitative research method and usesa descriptive approach that aims to provide a systematic description of the ongoingsituation in the object of research that is the Management of Learning Facilities at theCommunity Learning Activity Center (PKBM) Mitra Riau Jaya Cemerlang MarpoyanDamai District Pekanbaru City. Data obtained based on the subject of researchers orinformants of researchers as many as 3 informants. As a reference for conductingresearch in the field, researchers prepare a grid in the form of a question format topresent interview material to respondents. The results of this study regarding theManagement of Learning Facilities in the Community Learning Activity Center (PKBM)of Riau Jaya Cemerlang, Marpoyan Damai District, Pekanbaru City have been carriedout quite well but there are still shortcomings, starting fromKey Words: Management, Learning Facilities